Pengaruh Kualitas, Ketersediaan dan Inovasi Produk terhadap Keputusan Pembelian di PT Sri Indah Mandiri Batam - Friendy, Friendy; Wasiman, Wasiman (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study investigates the influence of product quality, availability, and innovation on consumer purchasing decisions at PT Sri Indah Mandiri Batam, a leading construction material distributor facing issues in product returns, limited stock readiness, and insufficient innovation. The research aims to determine the extent to which each of these three variables affects purchase decisions. Employing a quantitative descriptive method, the study involved 172 respondents selected from a population of 301 using simple random sampling and the Slovin formula. Data were collected through structured questionnaires and analyzed using SPSS 26. The analysis included validity and reliability tests, classical assumption testing, multiple linear regression, and hypothesis testing. The results revealed that product quality, availability, and innovation significantly and positively influence purchasing decisions both partially and simultaneously. The standardized coefficients indicate that availability (34.2%) had the highest impact, followed by product quality (26.7%) and innovation (20.1%). The model's adjusted R² value of 0.739 suggests that these three variables explain 73.9% of the variance in consumer purchase decisions. These findings highlight the strategic importance of ensuring consistent product quality, stock availability, and proactive product innovation in sustaining competitive advantage and consumer loyalty.